2014
DOI: 10.1002/term.1917
|View full text |Cite
|
Sign up to set email alerts
|

Horseradish peroxidase-catalysedin situ-forming hydrogels for tissue-engineering applications

Abstract: In situ-forming hydrogels are an attractive class of implantable biomaterials that are used for biomedical applications. These injectable hydrogels are versatile and provide a convenient platform for delivering cells and drugs via minimally invasive surgery. Although several crosslinking methods for preparing in situ forming hydrogels have been developed over the past two decades, most hydrogels are not sufficiently versatile for use in a wide variety of tissue-engineering applications. In recent years, enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 53 publications
2
91
0
Order By: Relevance
“…[10][11][12][13][14] Under the catalysis of HRP, phenol moieties of precursor polymers were oxidized by H 2 O 2 to form CAC crosslinks at ortho positions of benzyl rings or CAO between ortho-C and oxygen atoms of hydroxyl groups to form hydrogels. [15] The chitosan-PEG hydrogels achieved the high adhesive strength and the effective hemostatic property, [10] but their cell-inert behavior limited them in extending to cell delivery applications. To overcome this limitation, the hydroxyphenyl propionic acid-conjugated gelatin (GH) hydrogels containing the inherent RGD peptide being favorable to cells were developed.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Under the catalysis of HRP, phenol moieties of precursor polymers were oxidized by H 2 O 2 to form CAC crosslinks at ortho positions of benzyl rings or CAO between ortho-C and oxygen atoms of hydroxyl groups to form hydrogels. [15] The chitosan-PEG hydrogels achieved the high adhesive strength and the effective hemostatic property, [10] but their cell-inert behavior limited them in extending to cell delivery applications. To overcome this limitation, the hydroxyphenyl propionic acid-conjugated gelatin (GH) hydrogels containing the inherent RGD peptide being favorable to cells were developed.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism presumably follows phenolic radical dimerization as in the HRP/H 2 O 2 system, where more stable ring residing phenoxy radicals dimerize to form the C-C bonded dimer and a ring residing radical dimerizes with an oxygen residing radical to form the less common C-O dimer. [36, 37, 42, 53–55] While it has been suggested that other photosensitizers, that operate through a similar mechanism, can be used to photodynamically generate dityramine only riboflavin is considered in this work. [53]…”
Section: Resultsmentioning
confidence: 99%
“…[41] TA-HA hydrogels are generally formed through reaction with hydrogen peroxide and horseradish peroxidase (HRP). [36, 39, 42] The mechanical properties of TA‐HA hydrogels fabricated through this enzymatic route are tunable by changing the concentrations of HRP and hydrogen peroxide. [35] While use of HRP/H 2 O 2 is the most common method used to crosslink TA in TA-substituted polymers, others have reported TA-hydrogel fabrication using light and tris(2,2′-bipyridyl)dichlororuthenium(II) hexahydrate, [Ru(bpy) 3 ]Cl 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HRP catalyzes the decomposition of hydrogen peroxide (H 2 O 2 ) in the presence of a reducing phenol moiety on a polymer precursor backbone, which is converted to a radical product. One equivalent of H 2 O 2 induces the formation of two aromatic radicals, which are readily coupled by a covalent bond to form a crosslinked structure under mild conditions . To ensure effective hydrogel formation, the most suitable molar ratio between H 2 O 2 and tyramine (TYR), as the phenol moiety, was found to be 0.5 …”
Section: Introductionmentioning
confidence: 99%